Schwann cell C5aR1 co-opts inflammasome NLRP1 to sustain pain in a mouse model of endometriosis - Mustafa Titiz; Lorenzo Landini; Daniel Souza Monteiro de Araujo; Matilde Marini; Viola Seravalli; Martina Chieca; Pasquale Pensieri; Marco Montini; Gaetano De Siena; Benedetta Pasquini; Silvia Vannuccini; Luigi Francesco Iannone; et al. (Nature Communications)
Abstract Over 60% of women with endometriosis experience abdominopelvic pain and broader pain manifestations, including chronic back pain, fibromyalgia, chronic fatigue, vulvodynia, and migraine. Although the imbalance of proinflammatory mediators, including the complement component C5a, is associated with endometriosis-related pain, the mechanisms causing widespread pain and the C5a role remain unclear. Female mice and women with endometriosis exhibit increased plasma C5a levels and pain. We hypothesize the Schwann cells involvement in endometriotic pain. Here, we show that silencing the C5a receptor (C5aR1) in Schwann cells blocks the C5a-induced activation of the NLRP1 inflammasome and subsequent release of interleukin-1β (IL-1β). Macrophages, recruited to sciatic/trigeminal nerves by IL-1β from Schwann cells, increase oxidative stress, which activates the proalgesic TRPA1 pathway, resulting in widespread pain. These findings reveal a pathway involving Schwann cell C5aR1, NLRP1/IL-1β activation, macrophage recruitment, oxidative stress, and TRPA1 engagement, contributing to pain in a mouse model of endometriosis.